Mussel-inspired codepositing interconnected polypyrrole nanohybrids onto cellulose nanofiber networks for fabricating flexible conductive biobased composites. (1st February 2019) - Wang, Zhong; Zhao, Shujun; Huang, Anmin; Zhang, Shifeng; Li, Jianzhang
Graphical abstract: Highlights: Mussel-inspired co-modification and interfacial synthesis strategy were introduced. Hybrid adhesion layer was proposed in constructing interconnected networks. Multiple interfacial interactions regulated networks bonded effectively. SPI composites exhibit significantly enhanced electrical and mechanical properties. Abstract: The exploitation of an efficient strategy for preparing flexible green conductive composites with an interconnected filler network is of great scientific and technical interest. Herein, a high-performance interconnected cellulose nanofiber (CNF) template functionalized tannic acid (TA)/polypyrrole (PPy) nanohybrid network (TPy@CNF) is fabricated by a green mussel-inspired co-modification approach. The network offers high electrical conductivity to prepare flexible, plant-derived soy protein isolate (SPI) composites. The mussel-inspired interface design demonstrates versatile functions of a reactive adhesion layer to construct a multiple-bond-regulated interconnected TPy@CNF conductive polymer network architecture without the need for harsh conditions and toxic reagents. This well-defined conducting TA/PPy-encapsulated CNF network is of great benefit in achieving strong synergistic interactions by enhancing electrical conductivity, reducing junction contact resistance, and ensuring efficient load transfer during bending. When integrating 7.5 wt% TPy@CNF, the prepared SPI composites deliver significantly enhanced conductivity of 0.078 S  m −1 along with superior mechanical robustness (improved tensile strength and toughness) and excellent structural stability. This interconnected network design strategy can provide a green yet feasible approach for elaborate construction of CNF/conducting polymers in advanced energy-storage technologies.